Modelling study of the precipitation and agglomeration behavior of metallic iron in coal slag and its effect on the slag viscosity under Shell coal gasification atmosphere - Chong HE; Jing GUO; Yuhong QIN; Lingxue KONG; Jin BAI; Wen LI (Meitan xuebao, 2023)
The minerals in coal are transformed to the coal slag during the entrained-flow coal gasification process. The stable operation of the gasifier relies on the smooth slag tapping process. The flow behavior of coal slag is quantified by the viscosity. The high-iron coal (w(Fe2O3)>15%, ash basis) is widely distributed in China. The iron (Fe2+ or Fe3+) in the coal slag is easily transformed to the metallic iron due to the high content of the reducing gas in the Shell coal gasifier. The presence of metallic iron may lead to the slag blockage or even the unscheduled shut-down of coal gasifier. Hence, it is necessary to investigate the metallic iron precipitation behavior and its effect on coal slag viscosity. The precipitation behavior of metallic iron is investigated by the thermodynamic modelling. Then, the kinetic models of the metallic iron precipitation and agglomeration are built, respectively. Finally, the effects of metallic iron on the crystallization and viscosity of coal slag are quantified. The metallic iron is precipitated under the Shell coal gasifier atmosphere. The high-CaO coal slag favors the metallic iron formation. The metallic iron precipitation model is built based on the diffusion behavior of the reducing gas in the coal slag. In contrast, the metallic iron agglomeration model is established according to the sedimentation of metallic iron particles in the liquid coal slag. Both increasing the CaO content of coal slag and employing high slagging temperature results in the drop of slag viscosity, and the low slag viscosity improves the iron reduction process and metallic iron sedimentation. Therefore, the precipitation and agglomeration of metallic iron are improved. The critical time (tc) of metallic iron agglomeration is proposed and is used as the guide to prevent the metallic iron agglomeration. The metallic iron agglomeration can be alleviated by decreasing the slag tapping temperature or reducing the CaO content of coal slag. The traditional KJMA model is modified by considering the thermodynamic equilibrium content of solid phase in the slag. The metallic iron induces the strong crystallization of anorthite in slag and the slag viscosity is therefore significantly increased. The time of slag viscosity increasing to 25 Pa·s is decreased with the slag tapping temperature, while the time of the solid content achieving the thermodynamic equilibrium is increased. The study demonstrates that the metallic iron precipitation and agglomeration can be alleviated by adopting a low slag tapping temperature, or by using the silicon-rich additive, or co-gasifying with the high-silicon coal during the entrained-flow gasification of high-iron coal.